Ballast water management system: Assessment of chemical quality status of several ports in Adriatic Sea. (October 2019) - Romanelli, G.; Berto, D.; Calace, N.; Amici, M.; Maltese, S.; Formalewicz, M.; Campanelli, A.; Marini, M.; Magaletti, E.; Scarpato, A.
Abstract: Oxidant treatment of ballast water (BW) is commonly used in BW systems in order to minimize the transport of alien species. The release of disinfection by-products (DBPs) associated to the treatment of BW and cross-contamination of butyltin (BT) compounds through BW discharge is a topic of environmental concern. A chemical port baseline survey has been conducted in seven ports of the Adriatic Sea. Analysis have been performed on transplanted mussels, surface sediment, seawater, BW. Results showed an evidence of BT contamination, particularly in sediments, probably related to their illegal usage or to intensive shipping activities. Therefore, BW may act as a vector and contribute to re-buildup of BT contamination in the coastal regions. A baseline set of data concerning DBPs is provided, showing the preferential distribution of these compounds in the marine environment that will be useful for future considerations on monitoring and assessment of chemical contamination associated with BW. Highlights: Chemical port baseline survey in seven Adriatic ports was carried out. Butyltin compounds associated with transport of ballast water was studied. Disinfection by-products associated with ballast waters treatment were evaluated.